Imaging of growth factors on a human tooth root canal by surface-enhanced Raman spectroscopy - Ranc, Václav; Žižka, Radovan; Chaloupková, Zuzana; Ševčík, Juraj; Zbořil, Radek (Analytical and bioanalytical chemistry, 2018)
Endodontic treatment of immature permanent teeth with necrotic pulp poses several clinical challenges and is one of the most demanding interventions in endodontics. Recently, with new discoveries in the field of tissue engineering, novel treatment protocols have been established. The most promising treatment modality is revascularization, whose integral part is the exposure of collagen matrix and embedded growth factors. However, optimization of the treatment protocol requires a development of analytical procedures able to analyze growth factors directly on the sample surface. In this work, method based on surface-enhanced Raman spectroscopy (SERS) was developed to investigate the influence of the time of the medical treatment using EDTA on exposure and accessibility of the growth factors, namely TGF-ß1, BMP-2, and bFGF on the dentine surface. The nanotags, which consist of magnetic Fe3O4@Ag nanocomposite covalently functionalized by tagged antibodies (anti-TGF-ß1-Cy3, anti-BMP-2-Cy5, and anti-bFGF-Cy7), were employed as a SERS substrate. Each antibody was coupled with a unique label allowing us to perform a parallel analysis of all three growth factors within one analytical run. Developed methodology presents an interesting alternative to a fluorescence microscopy and in contrary allows evaluating a chemical composition and thus minimizing possible false-positive results. Graphical abstract.
Keywords: dentin; Dentin; nanokompozity; Spectrum Analysis, Raman; Nanocomposites; Ferrosoferric Oxide; Imaging; stříbro; Silver; Growth factors; Transforming Growth Factor beta; Bone Morphogenetic Protein 2; transformující růstový faktor beta; kavita zubní dřeně; Humans; oxid železnato-železitý; fibroblastový růstový faktor 2; Fibroblast Growth Factor 2; Dental Pulp Cavity; SERS; kostní morfogenetický protein 2; Ramanova spektroskopie; lidé